The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/trc2.12284
|View full text |Cite
|
Sign up to set email alerts
|

Early Alzheimer's disease‐like reductions in gray matter and cognitive function with aging in nonhuman primates

Abstract: Introduction Age‐related neuropathology associated with sporadic Alzheimer's disease (AD) often develops well before the onset of symptoms. Given AD's long preclinical period, translational models are needed to identify early signatures of pathological decline. Methods Using structural magnetic resonance imaging and cognitive assessments, we examined the relationships among age, cognitive performance, and neuroanatomy in 48 vervet monkeys (Chlorocebus aethiops sabaeus) ranging from young adults to very old. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…We focused our image analysis on those commonly studied brain regions most affected by aging and AD-related pathology in NHPs , and humans . To identify these regions, magnetic resonance imaging (MRI) was used to acquire anatomical images of all four monkeys.…”
Section: Methodsmentioning
confidence: 99%
“…We focused our image analysis on those commonly studied brain regions most affected by aging and AD-related pathology in NHPs , and humans . To identify these regions, magnetic resonance imaging (MRI) was used to acquire anatomical images of all four monkeys.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Latimer et al showed that vervets and other NHP are promising models for exploring early-stage disease mechanisms and biomarkers and testing new therapeutic strategies [153]. These monkeys have the propensity to develop diseases relevant to humans during aging without genetic handling [154]. However, there are several limitations; vervets show amyloid deposits but do not have neurofibrillary tangles or tauopathy; therefore, they do not present generalized neurodegeneration.…”
Section: In Vivo Animal Models Of Admentioning
confidence: 99%
“…80 In vervet monkeys, their cortical grey matter volume and temporal-parietal cortical thickness was negatively associated with age, potentially increasing the risk of cognitive decline. 81 In general, naturally aging NHPs demonstrate human-AD resembling proteopathies, glial activation, but severe brain atrophy and cognitive decline is rarely observed, striking our interest into the protective mechanism preventing severe demented symptoms from occurring.…”
Section: Brain Atrophy/neurodegeneration In Aged Nhpsmentioning
confidence: 99%
“…75 Similar age-related brain volume changes in young and old vervet monkeys were also reported using MRI. 81 Additionally, MRI has been used to examine amyloid-related imaging abnormalities, a potentially serious side effect in clinical trials for AD that is closely associated with CAA. Aged squirrel monkeys showed both edematous and hyperintense types of amyloid-related imaging abnormalities, accompanied by reactive astrocytosis, microgliosis, infiltration of systemic inflammatory/immune cells, damage to axons and myelin, and hemosiderin deposition.…”
Section: Brain Imagingmentioning
confidence: 99%